2015
DOI: 10.1039/c4tb01819b
|View full text |Cite|
|
Sign up to set email alerts
|

Bacterial cellulose–hyaluronan nanocomposite biomaterials as wound dressings for severe skin injury repair

Abstract: Bacterial cellulose (BC), a network of pure cellulose nanofibers with fine crystallinity, high mechanical strength and wet capability, and good biocompatibility, is a good material candidate for wound dressing. Hyaluronan (HA) has obvious curative properties, promoting the healing of wound skin tissue and reducing scar formation. This study explored an ''orifice plate'' culture method to obtain BC samples of different sizes but consistent thicknesses. Novel BC-HA nanocomposites with a 3-D network structure wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
54
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(60 citation statements)
references
References 47 publications
3
54
2
1
Order By: Relevance
“…BC, in a wet state, is very soft, and easily forms an intimate contact with the skin, owing to its flexible and controllable shape properties. An evidence for this can be seen clearly in the example wherein a severe second‐degree burn wound was completely healed with BC treatment for 44 days . Prior to its use as a wound dressing material; several approaches can be used to manipulate BC in its pure form, in order to fulfill specific requirements.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…BC, in a wet state, is very soft, and easily forms an intimate contact with the skin, owing to its flexible and controllable shape properties. An evidence for this can be seen clearly in the example wherein a severe second‐degree burn wound was completely healed with BC treatment for 44 days . Prior to its use as a wound dressing material; several approaches can be used to manipulate BC in its pure form, in order to fulfill specific requirements.…”
Section: Introductionmentioning
confidence: 99%
“…These include structural changes, chemical reactions, or inclusion of secondary components. A previous study showed that modification of BC with hyaluronan enhanced the growth of primary human fibroblast cells to a greater extent than pure BC did, and resulted in faster wound healing . Other studies have shown that addition of the drug vaccarin to BC membranes increased its malleability, as indicated by the increase in elongation as compared to BC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The commercially available products mainly have two categories. One is based on natural biomaterials, for examples, chitin (Jayakumar, Prabaharan, Sudheesh, Nair, & Tamura, ), chitosan (Anjum, Arora, Alam, & Gupta, ), hyaluronic acid (Li et al, ), and so forth. They have good biocompatibility, but usually lack skin‐like elasticity and water resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to other biologic support materials, no by‐products that might cause cytotoxicity or reduce biocompatibility are generated during the production of BC by Acetobacter xylinum ( A. xylinum ) . This makes the use of the produced BC relatively easy and even more cost effective.…”
mentioning
confidence: 99%